Impact of ocean acidification on the early development and escape behavior of marine medaka (Oryzias melastigma). (October 2017) - Wang, Xiaojie; Song, Lulu; Chen, Yi; Ran, Haoyu; Song, Jiakun
Abstract: Ocean acidification is predicted to affect a wide diversity of marine organisms. However, no studies have reported the effects of ocean acidification on Indian Ocean fish. We have used the Indian Ocean medaka ( Oryzias melastigma ) as a model species for a marine fish that lives in coastal waters. We investigated the impact of ocean acidification on the embryonic development and the stereotyped escape behavior (mediated by the Mauthner cell) in newly hatched larvae. Newly fertilized eggs of medaka were reared in seawater at three different partial pressures of carbon dioxide ( p CO2 ): control at 450 μatm, moderate at 1160 μatm, and high at 1783 μatm. Hatch rates, embryonic duration, and larval malformation rates were compared and were not significantly different between the treatments and the control. In the high p CO2 group, however, the yolks of larvae were significantly smaller than in the control group, and the newly hatched larvae were significantly longer than the larvae in the control. In the moderate p CO2 group, the eye distance decreased significantly. No significantly negative growth effects were observed in the larvae when exposed to p CO2 levels that are predicted as a result of ocean acidification in the next 100–200 years. Larvae reared under control conditions readily produced C-start escape behavior to mechanosensory stimuli; however, in the moderate and high p CO2 experimental groups, the probabilities of C-start were significantly lower than those of the control group. Therefore, the sensory integration needed for the C-start escape behavior appears to be vulnerable to ocean acidification. Altered behavior in marine larval fish, particularly behaviors involved in escape from predation, could have potentially negative implications to fish populations, and, further, to the marine ecosystems at the levels of CO2 projected for the future. Graphical abstract: Highlights: No significantly negative growth effects were observed in larvae exposed higher p CO2 . Eye defects and abnormal development of brain were obvious in exposed larvae. Escape behavior was vulnerable to ocean acidification.